Pathophysiological Significance of WDR62 and JNK Signaling in Human Diseases - Zhi, Yiqiang; Zhou, Xiaokun; Yu, Jurui; Yuan, Ling; Zhang, Hongsheng; Ng, Dominic C. H.; Xu, Zhiheng; Xu, Dan (Frontiers in Cell and Developmental Biology, 2021)
The c-Jun N-terminal kinase (JNK) is highly evolutionarily conserved and plays important roles in a broad range of physiological and pathological processes. The WD40-repeat protein 62 (WDR62) is a scaffold protein that recruits different components of the JNK signaling pathway to regulate several human diseases including neurological disorders, infertility, and tumorigenesis. Recent studies revealed that WDR62 regulates the process of neural stem cell mitosis and germ cell meiosis through JNK signaling. In this review we summarize the roles of WDR62 and JNK signaling in neuronal and non-neuronal contexts and discuss how JNK-dependent signaling regulates both processes. WDR62 is involved in various human disorders via JNK signaling regulation, and may represent a promising therapeutic strategy for the treatment of related diseases.